The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2214/ajr.06.1290
|View full text |Cite
|
Sign up to set email alerts
|

Automated Breath-Hold Perfusion SPECT/CT Fusion Images of the Lungs

Abstract: DIBrH SPECT is acceptable for routine application to improve respiratory motion effects and accuracy of SPECT/CT image fusion. Confirmative perfusion-morphologic correlation with reliable fusion images appears useful for clarifying the cause of perfusion defects and abnormal lung CT attenuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…Conversely, in 4 other patients who did not have PE in vessels in the lung territory, perfusion defects were observed in the territory despite the absence of PE from the branches (50). There was, therefore, an unexpected dissociation between the localized PE and lung perfusion defects in some patients (50), although correlation with fusion images previously appeared useful for clarifying the cause of perfusion defects (51).…”
Section: Technical Studiesmentioning
confidence: 89%
“…Conversely, in 4 other patients who did not have PE in vessels in the lung territory, perfusion defects were observed in the territory despite the absence of PE from the branches (50). There was, therefore, an unexpected dissociation between the localized PE and lung perfusion defects in some patients (50), although correlation with fusion images previously appeared useful for clarifying the cause of perfusion defects (51).…”
Section: Technical Studiesmentioning
confidence: 89%
“…These characteristics are especially suitable for oncology [14,[104][105][106][107][108] where detailed anatomical localization is needed. Other investigators have reported using the higher-performance SPECT/CT systems for applications in orthopedics [129][130][131][132], infection and inflammation [133][134][135][136][137][138], pulmonary function [139,140], and endocrinology [141], where the improved anatomical localization helps identify areas of disease that can be difficult to discriminate with SPECT alone. As previously mentioned, high-resolution CT performance also can be used to define target anatomy to improve the quantitation of absolute radionuclide uptake in small lesions such as tumors or in the myocardium.…”
Section: Current Spect/ct Technologiesmentioning
confidence: 99%
“…Clinical Applications of SPECT/CT Cited Anatomical/Disease Site Radiopharmaceutical SPECT/CT Application Adrenal masses 123 I-metaiodobenzylguanidine, 75 Se-cholesterol Anatomical localization [161] Biliary leak 99m Tc-diisopropyl iminodiacetic acid Anatomical localization [141] Bone scintigraphy 99m Tc-methylene diphosphonate, 99m Tc-dicarboxypropane diphosphonate Anatomical localization, attenuation correction [162][163][164][165][166][167][168][169] Brain cancer 99m Tc-tetrofosmin Anatomical localization [170] Breast cancer 99m Tc-sestamibi Anatomical localization [171] Colorectal cancer 99m Tc-labelled macroaggregated albumin Hepatic artery infusion of chemotherapy [172] Coronary artery calcification 99m Tc-tetrofosmin Head/neck cancer L-3-123 I-iodine-alpha-methyl-tyrosine, 123 I-labeled L19(scFv)2 antibody Anatomical localization [175][176][177] Hepatic haemangioma 99m Tc-labelled red blood cells Anatomical localization [178,179] Hepatic carcinoma 99m Tc-macroaggregated albumin Anatomical localization [180] Human immunodeficiency virus (HIV) 99m Tc-sulfur colloid Anatomical localization of microbicide surrogate [138] Infection Gallium-67, 111 In-labeled leukocytes Anatomical localization [133][134][135][136] Left ventricular function 99m Tc-tetrofosmin Regional wall motion evaluation, myocardial muscle mass, ejection fraction, cardiac volumes [118] Lung (ventilation/perfusion) 99m Tc-Technegas, 99m Tc-macroaggregated albumin Anatomical localization and registration of ventilation-perfusion patterns [139,140] Lung cancer 99m Tc-sestamibi, 99m Tc-depreotide Anatomical localization [181][182]…”
mentioning
confidence: 99%
“…It also degrades image sharpness and smears ill-defined perfusion defects [10][11][12][13]. The recently developed deep-inspiratory BrH (DIBrH) SPECT can improve these adverse lung motion effects and provides reliable SPECT-CT fusion images [14][15][16].…”
Section: Introductionmentioning
confidence: 99%